Socioeconomic Differences in the Association Between Competitive Food Laws and the School Food Environment1. (September 2015) - Taber, Daniel R.; Chriqui, Jamie F.; Powell, Lisa M.; Perna, Frank M.; Robinson, Whitney R.; Chaloupka, Frank J.
ABSTRACT BACKGROUND Schools of low socioeconomic status (SES) tend to sell fewer healthy competitive foods/beverages. This study examined whether state competitive food laws may reduce such disparities. METHODS School administrators for fifth‐ and eighth grade reported foods and beverages sold in school. Index measures of the food/beverage environments were constructed from these data. Schools were classified into SES tertiles based on median household income of students' postal zip code. Regression models were used to estimate SES differences in (1) Healthy School Food Environment Index (HSFEI) score, Healthy School Beverage Environment Index (HSBEI) score, and specific food/beverage sales, and (2) associations between state competitive food/beverage laws and HSFEI score, HSBEI score, and specific food/beverage sales. RESULTS Strong competitive food laws were positively associated with HSFEI in eighth grade, regardless of SES. Strong competitive beverage laws were positively associated with HSBEI particularly in low‐SES schools in eighth grade. These associations were attributable to schools selling fewer unhealthy items, not providing healthy alternatives. High‐SES schools sold more healthy items than low‐SES schools regardless of state laws. CONCLUSIONS Strong competitive food laws may reduce access to unhealthy foods/beverages in middle schools, but additional initiatives are needed to provide students with healthy options, particularly in low‐SES areas.